Low-Grade Fibromyxoid Sarcoma: A case report from Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2023)
Background: Low-Grade Fibromyxoid Sarcoma (LGFMS) is a rare sarcomasubtype predominantly affecting younger adults and typically presents in theextremities and trunk. It is characterized by an indolent clinical course.Case presentation: A-45-year woman presented with a large mass in the left lung based on chest-computed tomography (CT). A needle biopsy through chest wall from the mass and a bronchial endoscopy were done. She had a total left pneumonectomy and based on the pathology results, the tumor wasLGFMS, which was confirmed by immunohistochemistry staining and FISH study. The woman had a mass in the right thigh which was resected after a biopsy was done. This thigh mass was LGFMS. She received adjuvant chemotherapy treatment for two lines because of disease progression.Conclusion: LGFMS is characterized by its low sensitivity to both chemo-and radiotherapy. Surgical excision with clear resection margins is the first line treatment option.